Neurofibromatosis type 1: a case report - Marques, Ana Catarina (2013)
Introduction: Neurofibromatosis type 1 (NF1) is a common neurocutaneous condition with an autosomal dominant pattern of inheritance. A new mutation occurs in about half of the cases. The diagnosis is based on clinical assessment so family physicians should be aware of the manifestations of the disease. Case presentation: A 29 year-old female patient presented with a history of numerous skin lesions since childhood. The lesions were getting progressively worse. The patient also had learning disabilities. Her mother had similar skin lesions. She was referred to a General Surgery clinic in 2008 because of “multiple moles and warts”. After excision of skin lesions, a pathological diagnosis, of neurofibromas was made in 2009. She was referred to a Neurology clinic and the clinical diagnosis of NF1 was confirmed by the presence of neurofibromas, freckles, and more than 6 café au lait spots on the skin. It was also noted that her three year-old son had one café au lait patch on his skin. The child was referred to a Dermatology clinic in 2012. At this time the child fulfilled the clinical criteria for the diagnosis of NF1. Commentary: Because of the prevalence (1/2500-3000) and severity of complications of NF1, the early detection of the disease is important. As is evident in this case, clinicians are not always aware of its manifestations, missing opportunities for genetic counselling and preventing complications of the disease.